Waste biorefinery to produce renewable energy: Bioconversion process and circular bioeconomy - Shams Forruque Ahmed (17714472) (2023)
Continual global energy scarcity and its future challenges, as well as environmental disasters, are causing global devastation. Additionally, a substantial quantity of food is being wasted regularly. Therefore, the adoption of circular bioeconomy principles and the bioconversion of wasted food appears to be both highly advantageous and urgently required. However, previous studies have placed limited emphasis on the technological progress and circular bioeconomy aspects associated with the bioconversion of wasted food. The present review thus investigates how mass-generated food waste can be used to produce valuable bioproducts through bioconversion techniques such as oleaginous metabolism, anaerobic fermentation, and solventogenesis. These techniques have attracted considerable interest due to their eco-friendly and resource-recycling capacities, as well as their efficiency and sustainability. The paper also discusses approaches to integrate biorefineries within existing economies to establish a circular bioeconomy and analyses the challenges as well as the techno-economic, environmental and life cycle scenarios of these approaches. Analysis of the techno-economic and environmental effects reveals that food waste biorefineries can be lucrative if certain pathways are maintained. The environmental impact of bioconversion methods that produce valuable bioproducts is also found to be substantially lower than that of conventional methods. Integrating bioconversion processes further improves the efficiency of the process and sustainably recovers resources. Developing a circular bioeconomy requires the adoption of a biorefinery strategy with an integrated approach. Other Information Published in: Energy Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.egyr.2023.09.137